12(28-3x)+90(-30+3)=

Simple and best practice solution for 12(28-3x)+90(-30+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12(28-3x)+90(-30+3)= equation:


Simplifying
12(28 + -3x) + 90(-30 + 3) = 0
(28 * 12 + -3x * 12) + 90(-30 + 3) = 0
(336 + -36x) + 90(-30 + 3) = 0

Combine like terms: -30 + 3 = -27
336 + -36x + 90(-27) = 0

Multiply 90 * -27
336 + -36x + -2430 = 0

Reorder the terms:
336 + -2430 + -36x = 0

Combine like terms: 336 + -2430 = -2094
-2094 + -36x = 0

Solving
-2094 + -36x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2094' to each side of the equation.
-2094 + 2094 + -36x = 0 + 2094

Combine like terms: -2094 + 2094 = 0
0 + -36x = 0 + 2094
-36x = 0 + 2094

Combine like terms: 0 + 2094 = 2094
-36x = 2094

Divide each side by '-36'.
x = -58.16666667

Simplifying
x = -58.16666667

See similar equations:

| 426*15= | | -4x-2a= | | (.75)x+(.625)-(.5)x=(1.5)x-(2.5) | | (5x+2)/(4x+7)=x | | (5x+2)/(4x+7) | | (3/4)x-6=x+5 | | 1-1/x-8 | | 1+1/x-8 | | -8x+10=5x+9 | | 2(x-5)(x-5)=0 | | xx-2x+1=0 | | (3d-7)+8=0 | | 7/4u=1/2-1/6v | | y+-4y=118 | | 5x-(17*13)/122=2 | | (6y+5)+(2y-6)=118 | | (6y+5)+(2y-6)= | | 1x+20+2x=-10-2x-15 | | 16x+8x=192 | | 9+3x=14+2x | | (1800+x)/(25+y)=80 | | (3y+5)+(y-6)=118 | | 10cos(10x)=0 | | (-(-3x-5y)/4x)-((4x+9y)/4x)=0 | | 8x+4x=192 | | (7x+1)-(x-5)=6 | | 7x+1-5x=6 | | 2.5=(540-x)/x | | x+raiz(x-1)=13 | | 2.5X=540-x | | 2.5X=240-X | | y=14x^2-56 |

Equations solver categories